Association of Toxoplasma gondii Seropositivity and TNF-α -308G/A Polymorphism with Type 2 Diabetes Mellitus in Women - Firas Kareem Al-Kalabi Al-Kalabi (Universitas Muhammadiyah Sidaorjo, 2026)
General Background: Type 2 Diabetes Mellitus (T2DM) is a multifactorial metabolic disorder involving genetic and environmental components with chronic low-grade inflammation. Specific Background: Infectious agents such as Toxoplasma gondii and inflammatory cytokine gene variations, including TNF-α -308G/A polymorphism, have been investigated for their association with metabolic disturbances. Knowledge Gap: The combined relationship between T. gondii seropositivity and TNF-α genetic variation in women with T2DM remains insufficiently characterized. Aims: This study aimed to evaluate the association of T. gondii infection and TNF-α -308G/A polymorphism with T2DM in women. Results: In a case-control design involving 480 women, T2DM cases showed higher T. gondii IgG seropositivity (68.3% vs. 45.8%) and elevated IgG titers (47.3 ± 28.6 vs. 32.1 ± 24.8 IU/mL). Additionally, the A allele frequency of TNF-α -308G/A was higher in cases than controls (0.256 vs. 0.208; OR = 1.31, P = 0.047). Novelty: This study integrates parasitic infection status with inflammatory genetic polymorphism in a single analytical framework among women. Implications: Findings suggest that chronic infection and genetic susceptibility are associated with T2DM, supporting further investigation into inflammatory and infectious pathways in metabolic disorders. Highlights:• Higher IgG seroprevalence observed among diabetic participants• Elevated antibody titers indicate persistent parasitic exposure patterns• Allelic variation linked with increased disease susceptibility Keywords: Toxoplasma Gondii, Type 2 Diabetes Mellitus, TNF Alpha Polymorphism, Seropositivity, Case Control Study